Preliminary Study of the Seagrass Flora of Sabah, Malaysia. - Ismail, Norhadi (Universiti Putra Malaysia Press, 1993)
The species composition, distribution and the biomass of different seagrass beds along the coast of Sabah have been surveyed. Nine seagrass species belonging to six genera were recorded during the survey. Five of these i. e Cymodocea rotundata Ehrenb. et Hempr. ex Aschers., Cymodocea serrulata (R. Br.) Aschers. et Magnus, Halodule uninervis (Forssk.) Aschers., Halodule pinifolia (Miki) den Hartog and Syringodium isoetifolium (Aschers.) Dandy have not previously been reported from this area, thus represent new records for Sabah. The most frequently encountered species at the sampling stations was Halophila ovalis (R. Br.) JD. Hook followed by Thalassia hemprichii (Ehrenb.) Aschers and Enhalus acoroides (L.f) Royle. Seagrasses were observed from intertidal zone down to 2.5 m depth on various substrate types such as coral rubble, sand to muddy-sand. There was no specific zonation in the distribution of seagrasses. However, two zones may be distinguished according to the most abundant species. The seagrass beds in Sabah were also found to produce very high biomass particularly in the muddy habitat bordering mangroves (e.g. total biomass E. acoroides amounted to 468.5 g AFDWm·2 ). Among the seagrass beds around the off-shore islands such as Pulau Sipadan, T. hemprichii (146 g AFDW m·2 ) was found to be a very important biomass contributor.